The Implementation of GMP and SSOP at Semi-Dried Anchovy Fish Processing Units in Tuban - Mochamad Zainul Amin; Lilik Pujantoro Eko Nugroho; Nurjanah Nurjanah (Jurnal Pengolahan Hasil Perikanan Indonesia, 2018)
Anchovy is very abundant in Indonesian waters and become economically potential export commodity. The value of anchovy production in Indonesia increased from Rp 1.222 billion in 2006 to Rp 3.095 billion in 2014. The anchovy processing industries in East Java are mainly found in Madura and Tuban. This study was aimed to identify the implementation levels of the GMP (Good Manufacturing Practice) and SSOP (Sanitation Standard Operating Procedures) of three semi-dried anchovy fish processing units(UPI) in Tuban. The application of GMP and SSOP in these three fish processing units was assessed using observation and interview. The research shows that the application of the GMP and SSOP at UPI A andUPI B did not fulfill the regulation of the Minister of Industry of the Republic of Indonesia in 2010. Many components such as the building condition and layout, solid waste management, environmentalmanagement and personal management are still not fulfilled the standard. Meanwhile, UPI C in general have fulfilled the Regulation of the Minister of Industry of the Republic of Indonesia in 2010.